PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE, TINGKAT SUKU BUNGA DAN PERINGKAT OBLIGASI TERHADAP YIELD TO MATURITY OBLIGASI - Ruth Samatha Hamzah (AKUNTABILITAS, 2014)
This study is aimed to give better understanding the impact of Good Corporate Governance (GCG) implementation, interest rate, and bond rating on bond Yield to Maturity (BYTM) through controlled variable namely Debt to Equity Ratio (DER) and Return on Equity (ROE). BYTM is an indicator for the investors to foresee the future value of the bond until its payment due. In order to predict how marketable a bond is, investor must consider an array of aspects, be it internally (GCG and rating) or externally (interest rate).GCG variables that had been set in this study consists of four proxies, namely institutional ownership, managerial ownership, the size of independent supervisory board, and audit commitee. During a period of 2010-2012, 84 bonds from 16 companies were sampled in this study. This study employed panel regression method to analyze the data. The results of this study has shown that proxies from GCG variables, namely institutional ownership, managerial ownership, the size of independent supervisory board, and audit commitee, impart significantly negative effects on BYTM, whereas audit commitee gives unsignificantly positive impact. Interest rate and bond rating impart significantly positive and significantly negative impacts, respectively. Controlled variables of DER and ROE does not give significant effects.